Simulasi Aplikasi Monitoring Kereta Api Berbasis Android - Faisal, Natriya; Sunardi, Sunardi (Politeknik Perkeretaapian Indonesia Madiun, 2020)
The train is a mass transportation mode that prioritizes timeliness and is scheduled in the operation of railways. This research aims to make it easier for consumers to see the realization of the train journey digitally by using the Delphi program developer. Program input comes from the coordinates detected by the GPS module and then sent to the database by the NodeMCU wifi module. The database used is the MySQL database type. Primary data used in the form of a coordinate point of the station to be passed as well as a simulation of the coordinate point that will be passed by the module. This research was conducted in stages following the Linear Sequential Model (LSM), which consisted of 4 repetitive stages, namely the stages of analysis and study of literature, design, assembly (hardware-assembly), and coding (coding-software), and testing. Testing is done through simulation and direct application on the customer. NodeMCU and GPS module programming use to help of Arduino IDE software suitable to connect modules to the database. Then the database will be linked to the viewer application that will be created with the Delphi program developer